The effect of addition of melon (Cucumis melo L.) flesh juice into Lactated Ringer's-egg yolk extender on spermatozoa plasma membrane integrity and spermatozoa morphological abnormalities of semen of native rooster - Pitaloka, Dinda Galuh; Mas'ud Hariadi; Suherni Susilowati; Budi Utomo; Tatik Hernawati; Eka Pramyrtha Hestianah; Samuel Inioluwa Akeju (Ovozoa: Journal of Animal Reproduction, 2023)
This study aims to determine the effect of adding melon (Cucumis melo L.) juice to Lactated Ringer's-egg yolk extender on the intact plasma membrane (IPM) and morphological abnormalities of native rooster spermatozoa. Five ejaculate each from two native roosters (Gallus gallus domesticus) were divided into four equal volumes. Ejaculate was extended 1:10 (v/v) in Lactated Ringer's-egg yolk without or with the addition of of 2, 4, and 8% (v/v) melon flesh juice, respectively for groups T0, T1, T2, and T3. Extended semen was stored in a refrigerator (5°C) and evaluated every two hours. The results showed that IPM of all groups decreased (p <0.05) consistently, lasting more than 40% for six hours in the T0 and T1 groups and four hours in the T2 and T3 groups. The percentage of spermatozoa morphological abnormalities in all groups stored for six hours was higher (p <0.05) than before storage. However, it was not significantly different (p >0.05) from that which had been stored for two and four hours. It was concluded that native rooster semen extended in Lactated Ringer's-egg yolk without (group T0) or with 2% melon flesh juice (group T1) and stored at 5°C retained spermatozoa plasma membrane integrity of more than 40% and morphological abnormalities of less than 20% for six hours. While the addition of 4 % (T2) and 8% (T3) melon flesh juice maintained the percentage of IPM and spermatozoa morphological abnormalities for only four hours.